Effectiveness of Octopus (Octopus sp.) Ink Extract on the Growth of Mozambique Tilapia (Oreochromis mossambicus) Infected with Aeromonas hydrophila - Elsa Sabathini; Rangga Idris Affandi; Awan Dermawan (Journal of Fish Health, 2026)
Mozambique tilapia (Oreochromis mossambicus) is an important aquaculture commodity in Indonesia; however, its productivity can be constrained by disease outbreaks, including Aeromonas hydrophila infection. The use of natural feed additives containing nutritional and bioactive compounds is a promising strategy to improve fish growth and health. This study aimed to evaluate the effectiveness of octopus (Octopus sp.) ink extract supplemented in feed on the growth performance of Mozambique tilapia infected with A. hydrophila. The study was conducted for 45 days using a completely randomized design with five treatments and three replications. The treatments consisted of a positive control, namely feed without octopus ink extract with A. hydrophila infection (K+); a negative control, namely feed without octopus ink extract and without A. hydrophila infection (K-); and feed supplemented with octopus ink extract at 50, 100, and 150 ml/kg feed followed by A. hydrophila infection (A, B, and C, respectively). The observed growth parameters were absolute weight gain, absolute length gain, specific weight growth rate, and specific length growth rate. The results showed that octopus ink extract supplementation improved all growth parameters compared with the positive control. The best performance was obtained in treatment B (100 ml/kg feed), with an absolute weight gain of 10.77±1.53 g, absolute length gain of 2.65±0.39 cm, specific weight growth rate of 2.59±0.11%/day, and specific length growth rate of 2.16±0.05%/day. Therefore, octopus ink extract has potential as a natural feed additive to enhance the growth performance of Mozambique tilapia challenged with A. hydrphila.